Influence of varying nitrogen levels on productivity, resource-use efficiency and profitability of summer mungbean (Vigna radiata L. wilczek) in Kandahar province of Afghanistan - Jalali, Mohammad Naim; Choudhary, Anil K. (Annals of Agricultural Research, 2019)
An experiment was conducted at the Experimental Farm of Afghanistan National Agricultural Sciences and Technology University (ANASTU), Kandahar during summer 2015 to study the effect of varying nitrogen levels on productivity, profitability and resource use efficiency of mungbean (Vigna radiata L. Wilczek) in semi-arid region of Kandahar, Afghanistan. Experimental treatments comprised of seven N levels (0, 10, 20, 30, 40, 50, 60 kg N ha–1 laid-out in a randomized complete block design with three replications. The results indicated that application of N @ 30 kg ha–1 exhibited highest root nodule count at maximum flowering, thereafter it decreased. There was a consistent and significant increase in grain and straw yield (1.96, 5.29 t ha–1) and production-efficiency (21.7 kg ha–1 day–1) upto 30 kg N ha–1, thereafter it also showed a declining trend upto 60 kg N ha–1. Higher water use efficiency, production efficiency, and monetary efficiency were recorded when N was applied @ 30 kg ha–1. However, the optimum nitrogen dose was calculated as 33.47 kg ha–1. Overall, it can be inferred that the application of N @ 30 kg ha–1 can be used as a blanked recommendation for obtaining higher productivity, resource-use efficiency and profitability in mungbean. But as a site-specific recommendation, the economic optimum N dose for mungbean is 33.47 kg N ha–1 which has great promises in enhancing the productivity, resource-use efficiency and profitability in summer mungbean (Vigna radiata L. wilczek) under semi-arid conditions of Kandahar region of Afghanistan.